Determinants of academic research productivity in Malaysia: an integration of theory of planned behaviour and social capital theory / Zahariah Sahudin ... [et al.] - Sahudin, Zahariah; Mustaffa, Abd Hadi; Abdullah, Hasni; Eko Pramono, Suwito; Wijaya, Atika; Melati, Inaya Sari (Universiti Teknologi MARA, 2023)
Academic research output in Malaysia has been on the rise for decades. However, despite the positives, the key difficulties are the absence of enough funding for research and lower research productivity compared to other countries. Hence, the objective of the study is to examine the determinants of academic research productivity in Malaysia. The combination of the Theory of Planned Behaviour (TPB) and Social Capital Theory (SCT) was applied in this study. 384 academicians’ responses were collected using a questionnaire, and PLS-SEM was the main analysis tool. The findings indicated that commitment, leadership, authority, academic integrity, technology, attitude, subjective norm, academic discipline, and knowledge behaviour significantly influence research productivity. However, management support and knowledge intention do not significantly influence research productivity. With this finding, the authors highlighted that TPB-SCT could be combined and extended to become an extended model to measure behaviour and productivity.